Identification of 16S rRNA genes in bacteriocin-producing bacteria - SUKMAWATI SUKMAWATI; SIPRIYADI SIPRIYADI; FEBRIANTI ROSALINA; RATNA RATNA; NURUL KUSUMA DEWI; MOHD IHWAN BIN ZAKARIAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sukmawati S, Sipriyadi, Rosalina F, Ratna, Dewi NK, Zakariah MIB. 2024. Identification of 16S rRNA genes in bacteriocin-producing bacteria. Biodiversitas 25: 3720-3727. The use of safe and effective biopreservatives in the food industry is highly important to extend the product shelf life and maintain the product quality without posing health risks. Bacteriocins, antimicrobial compounds produced by bacteria, offer biopreservatives potential that can inhibit the growth of pathogens and spoilage microorganisms in food products. Bacteriocins as biopreservatives in the food industry due to their antimicrobial properties and potential to enhance food safety and shelf life. Bacteriocins as biopreservatives are stable at high temperatures, which makes them suitable for various food processes. They are also stable across a broad pH range, ensuring their effectiveness in different food environments. This stability under various conditions instills confidence in their effectiveness. This study aimed to identify the 16S rRNA gene of bacteriocin-producing bacteria as an initial step in developing biopreservative candidates. This research method is a descriptive method that describes the types of bacterial species that are capable of producing bacteriocins. Bacteria were isolated from shrimp paste (cincalok), and genetic analysis was performed using PCR and sequencing techniques to identify the 16S rRNA gene. The bacterial samples derived from shrimp paste were identified as Bacillus paramycoides strain MCCC 1A04098 BSH 1, Bacillus albus strain MCCC 1A02146 BSH 2, and Bacillus cereus strain IAM 12605 BSH. All three samples are Gram-positive with bacilli-shaped cells, leading to the conclusion that these bacteria have the potential as biopreservatives.